Optimizing Financial Literacy to Increase Interest in Saving at Bank Syariah Indonesia - Komala, Adeh Ratna; Maryati, Mari; Balqis, Tania Indah; Benasifa, Citra Chintya (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
The low financial literacy of Indonesian society has an impact on the number of people who are trapped in fraudulent investments such as illegal pinjol. The purpose of this study was to determine the effect of financial literacy on interest in saving at BSI. The research method uses descriptive and verification using SEM PLS. The results showed that the financial literacy of BSI customers was in the good category, and the interest in saving was high. Financial literacy is proven to have a positive and significant effect on saving interest. Based on the results of the study, BSI is advised to increase practice-based financial education, such as workshops on the selection of Islamic savings products. Keywords: Financial literacy; saving interest; descriptive; verification; BSI